Algorithmic Biases in Health - Social-ethical challenges and perspectives - Hille, Eva Maria (ACM FAccT Conference, 2024)

Alles privat? Zur Ethik von Public Health und neuen Technologien - Hille, Eva Maria; Braun, Matthias (Public Health Forum, 2022)

Different Methods & Approaches of AI Ethics: Navigating AI Ethics to Practice - Bleher, Hannah; Hille, Eva Maria (Summer School "Artificial Intelligence, Ethics & Human Rights", 2022)
In the field of AI ethics, there are different approaches to how ethical theory can be put into practice. Each conceptual approach focuses differently on how to avoid a theory-practice gap and instead interweave both theory and practice. These different foci, such as a design-, principles- or stakeholder-orientation, however, have benefits and shortcomings. In this contribution, we provide an overview of current approaches of applied AI ethics and their opportunities and pitfalls. In addition to a systematization of conceptual approaches, specific aspects and methodological approaches are put up for discussion in order to interweave theory and practice of AI ethic

Ethical Design Science Research - An Interdisciplinary AI Ethics Framework - Hille, Eva Maria; Bleher, Hannah (ACM Konferenz "Fairness, Accountability and Transparency" (FAccT), 2025)

It’s just water?! Ethical reflections on theories of justice - Hille, Eva Maria (European School of Positive Impact and Responsibility (ESPOIR), 2022)

Meaningful Human Control over AI for Health? A Review - Hille, Eva Maria; Hummel, Patrik; Braun, Matthias (World Congress of Bioethics, 2024)

The impact of AI in health on social justice – reflections on the example of contactless sensor technology - Hille, Eva Maria (Sustainable AI Conference, 2023)

Using AI-based Sensor Technologies in Rheumatology. Ethical Considerations - Hille, Eva Maria (International Hand Symposium, 2023)

Verantwortung als zentrales Motiv einer Ethik der Künstlichen Intelligenz - Hille, Eva Maria (Digitale Tagung des neth:KI – Netzwerk für Theologie und KI: "Alexa, wie hast du’s mit der Religion? Technik, Digitalisierung und Künstliche Intelligenz im Fokus der Theologie", 2021)